German Laypeople’s Willingness to Donate Toward Insect Conservation: Application of an Extended Protection Motivation Theory - Dörge, Lara; Büscher, Milan; Drews, Jasmin; Eylering, Annike; Fiebelkorn, Florian (Frontiers in Psychology, 2022)
It is essential to engage the public in conservation measures to conserve insects. We investigate the Protection Motivation Theory (PMT), as well as knowledge, attitudes, and sociodemographic variables (gender, age, education level, and income) as predictors of willingness to donate and actual donations to insect conservation for a representative German sample (N = 515; MAge = 49.36, SD = 16.73; female = 50.1%). The PMT subcomponents severity, self-efficacy, and response efficacy, as well as attitudes toward insects, income, and education level, significantly predicted willingness to donate. In contrast, severity, response barriers, age, gender, and the willingness to donate significantly influenced actual donations. Overall, components of the PMT have high predictive power for both dependent variables. Our results suggest that an intention-behavior gap exists between the intention to donate and the actual donation toward insect conservation. Measures to increase willingness to donate and actual donations for insect conservation are discussed.